The announcement effect: Evidence from open market desk data - Òscar Jordà; Selva Demiralp; Holly Liu; Jeffrey Williams (University of California, Department of Economics, 2001)
This paper investigates the ability of the Federal Reserve to manipulate the overnight rate without open market operations (which Demiralp and Jorda (2000) term the announcement effect), using high-frequency, open-market-desk data. Using similar data, Hamilton (1997) takes advantage of forecast errors in the Treasury balance to compute the elasticity of the federal funds rate to these errors and thus to obtain a measure of the liquidity effect. Similarly, one can view daily deviations of the federal funds rate from target as forecast errors in the reserve need (see Taylor, 2000). By analyzing the manner and the type of operation the Fed uses to maintain the federal funds rate close to its targeted value and by observing the pattern of operations on the days surrounding a change in this target, we provide evidence of the announcement effect. Furthermore, we show that the discipline of the FOMC schedule dictates, not only the process of expectations formation in the overnight rate, but also the price adjustment process of term rates.
Keywords: E5; E4; C5; 330; open market operations; announcement effect; term structure; Ankündigungseffekt; Geldpolitik; Offenmarktpolitik; Geldmarkt; Zins; Liquiditätseffekt; USA